Unveiling the underlying molecular mechanisms of high lutein production efficiency in Chlorella sorokiniana FZU60 under a mixotrophy/photoautotrophy two-stage strategy by transcriptomic, physiological, and biochemical analyses - Ruijuan Ma; Zhen Zhang; Hong Fang; Xinyu Liu; Shih-Hsin Ho; Youping Xie; Jianfeng Chen (Biotechnology for Biofuels and Bioproducts, 2023)
Abstract Background Chlorella sorokiniana FZU60 is a promising lutein producing microalga. A mixotrophy/photoautotrophy two-stage strategy can achieve high biomass concentration at stage 1 and high lutein content at stage 2, leading to excellent lutein production efficiency in C. sorokiniana FZU60. However, the underlying molecular mechanisms are still unclear, restraining the further improvement of lutein production. Results In this study, physiological and biochemical analysis revealed that photochemical parameters (Fv/Fm and NPQ) and photosynthetic pigments contents increased during the shift from mixotrophy to photoautotrophy, indicating that photosynthesis and photoprotection enhanced. Furthermore, transcriptomic analysis revealed that the glyoxylate cycle and TCA cycle were suppressed after the shift to photoautotrophy, leading to a decreased cell growth rate. However, the gene expression levels of photosynthesis, CO2 fixation, autophagy, and lutein biosynthesis were upregulated at the photoautotrophy stage, demonstrating that microalgal cells could obtain more precursor to synthesize lutein for enhancing photosynthesis and reducing reactive oxygen species. Conclusions The findings help to elucidate the molecular mechanisms for high lutein production efficiency of C. sorokiniana FZU60 under the mixotrophy/photoautotrophy strategy, identify key functional genes responsible for lutein biosynthesis, and shed light on further improvement of lutein production by genetic or metabolic engineering in future studies.